Structural and electrical properties of BZT-added BNLT ceramics - Kantha P. (2014)
Lead free piezoelectric ceramics (1-x)BNLT-xBZT with x=0.00, 0.06, 0.09 and 0.12 were prepared using a two-step mixed oxide method. Dielectric, ferroelectric and piezoelectric properties of the ceramics were improved by the addition of the BZT. XRD results show tetragonal symmetry structure of the BNLT-BZT ceramics. It was found that the tetragonality increases with increasing BZT content. The optimum composition is x=0.09, where the maximum values of the piezoelectric constant d33 (~126 pC/N) and dielectric constant (~2400) were obtained at room temperature. This BNLT-BZT system can be a promising candidate for lead-free piezoelectric ceramics. © 2013 Elsevier Ltd and Techna Group S.r.l.